EXTRACȚIA ȘI IMPLEMENTAREA COLORANȚILOR NATURALI - Cojocaru, Ciprian; Ciocârlan, Alexandru (CEP USM, 2024)
This study aims to obtain and characterize natural dyes from local plant sources and agro-industrial waste for use in the food, cosmetic, and pharmaceutical industries. For this purpose, Soxhlet and combined extraction methods were employed, followed by sample concentration and recrystallization. The extraction involved multiple steps to ensure the purity and quality of the dyes. Microscopic and spectral (FT-IR) analyses confirmed the presence of the natural dyes and demonstrating their potential applications. The study highlights the importance of utilizing agro-industrial waste to create sustainable products, thereby reducing environmental impact and promoting the circular economy. By converting waste into valuable resources, this approach contributes significantly to the economic development and environmental sustainability of the Republic of Moldova, supporting local industries and creating new job opportunities.
EXTRACTION AND IMPLEMENTATION OF NATURAL DYES
Keywords: natural dyes; extraction; carotenoids; chlorophylls; anthocyanins; betalains